Propagação, cultivo e produção de óleo essencial de espécies de Lippia (Verbenaceae) ocorrentes no Semiárido Baiano - Bispo, Luma dos Passos (2015)
The genus Lippia (Verbenaceae) is characterized by having species with medicinal and aromatic properties, its economic potential aims to the production of essential oils with important biological and pharmacological activities. Even with all known diversity and potential, few species are the target of agronomic studies. Considering the propagation as the first step in the domestication of a species and the influence of external factors on essential oil production, this study aimed to evaluate the effect of cutting type and auxin concentrations in the vegetative propagation of the species L. insignis, L. lasiocalycina and L. thymoides, as well as different types of fertilization and harvest season in production, and content and chemical composition of the essential oil. In propagation tests two types of cuttings were used (apical and middle) and five IBA concentrations (0, 250, 500, 750 and 1000 mg L-1). In cultivation three forms of fertilization were tested (control, manure and manure + NPK 10:10:10) and two harvest seasons (210 and 360 days after planting). The essential oils are extracted from dry leaves by the hydrodistillation method by Clevenger apparatus, and chemical composition determined by gas chromatography with flame ionization detector (GC / FID) coupled to mass spectrometer (GC / MS). It was concluded that apical cuttings are the most suitable for the propagation of L. insignis and both apical and middle cuttings for L. thymoides and L. lasiocalycina; treatment with IBA is not necessary in the propagation by cuttings of these species; chemical fertilizers (NPK) associated with cattle manure was the best treatment in growth and biomass production of the species L. lasiocalycina and L. thymoides, while for L. insignis to the control treatment was the best; pruning, followed by the second growing season (regrowth) is recommended in the cultivation of the studied species, aiming at the production of essential oil; β-myrcene, limonene and E-ocimenone are the major components of L. insignis; β-myrcene and E-ocimenone the major components of L. lasiocalycina and E-caryophyllene and caryophyllene oxide the major components of L. thymoides; fertilization and harvest season promote quantitative variations in the chemical composition of essential oils; the species L. insignis and L. thymoides are the most promising for essential oil production in the conditions of Feira de Santana, Bahia, Brazil.